PENGARUH LINGKUNGAN KERJA DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA PALANG MERAH INDONESIA DI KOTA JAKARTA SELATAN - Nauval Naswa; Endang Suprapti (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to determine the effect of work environment and communication on employee performance at the Indonesian Red Cross in South Jakarta, both partially and simultaneously. The research type uses associative quantitative methods. The sample of this study consists of 75 respondents who are employees of PMI South Jakarta. Data analysis techniques used include data instrument testing, classical assumption testing, simple linear regression, multiple linear regression, correlation coefficient, and coefficient of determination. Hypothesis testing uses t-test and F-test. The analysis results show work environment partially affects employee performance with a simple linear regression equation of 11.870 + 0.711 X1. The correlation coefficient value is 0.721, meaning it has a strong relationship level, and the coefficient of determination is 0.520, meaning employee performance is influenced by work environment by 52%. This is proven by the t-test obtaining a t-calculated value > t-table (8.895 > 1.993) and strengthened by a significance value < 0.05 (0.000 < 0.05). Communication partially has a positive effect on employee performance, shown by the simple linear regression equation Y = 4.623 + 0.868 X2. The correlation coefficient value is 0.815, meaning it has a strong relationship, and the coefficient of determination is 0.664, meaning performance is influenced by communication by 66.4%. This is proven by the t-test obtaining a t-calculated value > t-table (12.010 > 1.993) and strengthened by a significance value < 0.05 (0.000 < 0.05). The research results of work environment and communication simultaneously on employee performance are shown by the multiple linear regression equation Y = 3.689 + 0.194 X1 + 0.701 X2, with a correlation coefficient value of 0.823, meaning it has a strong relationship level, and a coefficient of determination of 0.678, meaning performance is influenced by work environment and communication by 67.8%. This is proven by the hypothesis test results using F-test obtaining an F-calculated value > F-table (75.812 > 3.12) and strengthened by a significance value < 0.05 (0.000 < 0.05). Thus, it is proven that Ho is rejected and Ha is accepted.